A Practical Framework for ASFV Disinfectant Evaluation: Differentiating Cytopathic Effects from Cytotoxicity via Integrated Analytical Methods - Sok Song; Kyu-Sik Shin; Su-Jeong Kim; Yong Yi Joo; Bokhee Han; So-Hee Park; Hyun-Ok Ku; Wooseog Jeong; Choi-Kyu Park (Pathogens)
African swine fever virus (ASFV) is a highly virulent DNA virus that has spread globally since its introduction into Georgia in 2007, causing substantial economic losses in the swine industry. In the absence of an effective vaccine, chemical disinfection remains a key strategy for disease control. However, in cell-based disinfectant efficacy testing, distinguishing between disinfectant-induced cytotoxicity and virus-induced cytopathic effects (CPEs) remains a major challenge, leading to the potential misinterpretation of results. To address this, we developed a multi-step analytical framework to differentiate CPEs from cytotoxicity using a Vero cell-adapted ASFV strain. Virkon® S was tested at three dilutions—375×, 275× (manufacturer-recommended), and 175×—and evaluated through CPE observation, lactate dehydrogenase (LDH) and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays, and antigen detection via lateral flow immunoassay (p30) and immunofluorescence (p54). Notably, the 375× dilution achieved effective viral inactivation with significantly lower cytotoxicity, demonstrating that this framework can facilitate a more refined determination of disinfectant working dilutions. Furthermore, increased p30 signals after disinfection and the observation of lower cytotoxicity in virus-plus-disinfectant groups compared to disinfectant-only groups highlight the complexity of virus-disinfectant interactions and the potential for misinterpretation. This study provides a standardized and interpretable strategy for assessing ASFV disinfectant efficacy and offers a practical basis for evaluating other enveloped viruses in future disinfection studies.